FORMATION OF THE MANUSCRIPT COLLECTION OF THE MARTYNAS MAŽVYDAS NATIONAL LIBRARY OF LITHUANIA IN THE 8–9TH DECADES OF THE 20TH C. - STEPONAITIENĖ, JOLITA (Knygotyra, 2012)
Document collection, systematic and reasonable acquisition, and interests and needs of a certain organization are among its main functions. From the historical point of view, formation of a document collection reflects the actualities of the time, policies, understandings and public obligations of an institution. It could seem that the soviet ideology couldn’t disregard such library activities; however, exploring the documents of that time reveal some paradoxical things such as acquiring “ideologically wrong” documents. What was the motivation of these actions? What was their interpretation among colleagues? Research of material found in various sources shows that, despite the existing system, the acquisition of the National Library manuscript document collection was little influenced by common attitudes. The collection had been supplemented with documents of various historical periods, in various languages. Laconic and very general entries in the Document Acquisition Book let to hide the content of documents. The main sources of acquisition were purchasing and donations, purchasing being the most frequent source of acquisitions. A conclusion should be made that the library made investments to preserve historical documents, and the librarians responsible for these processes were aware of their importance.